The Best Rules for Knowing the Inferior Hadith - Mahdi , Muhammad (Islamic Sciences Journal, 2023)
The inferior hadiths about the Prophet, may Allah’s prayers and peace be upon him, are numerous and not known by every person other than the people of the hadith and its bearers. It is possible to know the inferior hadiths by laying down clear rules taken from what scholars have deduced through their knowledge of the words of our master, the Messenger of Allah, may Allah’s prayers and peace be upon him. The deliberate inferiority on our master, the Messenger of Allah, may Allah bless him and grant him peace, is considered one of the greatest sins. Whoever narrates hadiths made out of negligence, this is a sinner because he is not certain of the hadith, rather he is a participant in the sin of the one who lied our master, the Messenger of Allah, may Allah prayers and peace be upon him.